The Role of KKN MBKM Students in Increasing Knowledge of Disaster Response in Students of SDN 06 Buntulia: Peran Mahasiswa KKN MBKM Dalam Upaya Peningkatan Pengetahuan Tanggap Bencana Pada Siswa SDN 06 Buntulia - Yayu, Yayu Indriat Arifin; Nina, Ninasafitri; Siti Humaira Panigoro; Nur Sakina A. Gafar (Yayasan Ahmar Cendekia Indonesia, 2024)
This service activity focuses on efforts to increase the knowledge and understanding of students of SDN 06 Buntulia, Buntulia District, Pohuwato Regency, regarding disaster mitigation. The issue faced is the students' lack of understanding of the causes and ways to cope with disasters, even though they already have basic knowledge about natural disasters. The purpose of this activity is to provide education on disaster mitigation from an early age through the “Kencana Si Udin” program (Kenali Bencana Sejak Usia Dini). The methods used include interactive socialization and interesting material delivery, complemented by educational games to break the ice. In addition, simple technology in the form of flood-prone maps was introduced as part of the science and technology diffusion. This activity also involves collaboration with external parties to strengthen the implementation of socialization. The results showed an increase in students' knowledge of disaster mitigation, especially related to actions to be taken when a disaster occurs. It is hoped that socialization activities like this will continue to exist and develop by involving the community, especially children, to realize the importance of knowing disasters and disaster mitigation from an early age. Abstrak Kegiatan pengabdian ini berfokus pada upaya peningkatan pengetahuan dan pemahaman siswa SDN 06 Buntulia, Kecamatan Buntulia, Kabupaten Pohuwato, mengenai mitigasi bencana. Isu yang dihadapi adalah kurangnya pemahaman siswa tentang penyebab dan cara menanggulangi bencana, meskipun mereka sudah memiliki pengetahuan dasar tentang bencana alam. Tujuan dari kegiatan ini adalah memberikan edukasi mengenai mitigasi bencana sejak dini melalui program